From silver to cocaine : Latin American commodity chains and the building of the world economy, 1500-2000 - Topik, Steven; Marichal, Carlos; Frank, Zephyr L., 1970- (American encounters/global interactions., 2006)
Examining the commodity chains that have connected producers in Latin America with consumers around the world for 500 years, this work follows a specific commodity from its inception, through its development and transport, to its final destination in the hands of consumers.